The Influence of Price Perception and Product Quality on Luxcrime Cosmetics Purchase Decisions Post-Covid-19 Pandemic - Nabila Maharani Santika; Supriyono (International Journal of Asian Business and Management, 2023)
Using of cosmetics is very important to support people's appearance even in the post-COVID-19 pandemic era. This study aims to find out the effect of price perceptions and product quality on purchasing decisions for Luxcrime cosmetic products after the Covid-19 pandemic. The population in this study are consumers who have bought and used Luxcrime cosmetics since the new normal era with a minimum age of 17 years. The technique used in sampling is non-probability sampling with purposive sampling method with a sample size of 108 respondents. The analysis method uses Smart PLS software with Structural Equation Modeling (SEM) Techniques. The results of this study showed that: (1) Price perception has a significant positive effect of 0.427 on purchasing decisions; (2) Product quality has a significant positive effect of 0.417 on purchasing decisions